Study of discrepancies in ABO blood grouping: experience of a tertiary health-care center - Nathani, Kruti J.; Patel, Jitendra N.; Patel, Kamal A.; Wadhwani, Sangeeta J. (International Journal of Research in Medical Sciences, 2021)
Background: An accurate ABO grouping is the most important test which is done in the blood bank. Mistyping can lead to transfusion with ABO incompatible blood which results in severe intravascular haemolysis and may even result in the death of the recipient. An ABO discrepancy implies that the forward or red cell ABO grouping does not agree with the reverse or serum ABO grouping. The study was conducted to evaluate the frequency of ABO blood group discrepancies, to identified main causes of discrepancies, to avoid chances of wrong interpretation of blood group and to mitigate clinical impact associated with mismatch ABO transfusion. Methods: A prospective study of ABO discrepancies and their causes was performed on 25,129 samples of the patients and 13,251 samples of blood donors at the red cell serology laboratory in tertiary care teaching hospital and blood bank over the period from February 2017 to July 2018. Results: ABO group discrepancies were mainly divided in 4 different groups. Out of 51 discrepancies 32 (62.74%) were found in group-IV category, being highest amongst all; 10 (19.60%) in group-II which was second highest; other were 8 (15.69%) in group-I and 1 (1.96%) in group-III category. Conclusions: All discrepancies reported on ABO cell and serum grouping must be investigated further, so that correct blood group is reported, minimizing the chances of transfusion reaction. A note of caution should be mentioned on the blood group card to prevent ABO incompatibility in case of transfusion.